Analisis persepsi Generasi Z terhadap pembelian pakaian bekas pada sosial media di Indonesia - Julia, Sefira Rachma; Zunaedi, Rizqa Amelia; Putra, Perdana Suteja (Nur Science Institute, 2024)
The development of fashion trends in Indonesia is experiencing rapid growth; one of the growing trends in the fashion industry today is